Nonlinear pushover analysis of reinforced concrete columns and frame using rigid body spring discrete element method - Gregorio, Mark Jay M.
Rigid Body Spring Discrete Element Method (RBS-DEM) is proposed in this research for nonlinear static pushover analysis of reinforced concrete columns and reinforced concrete frame. A longitudinal springs (confined/unconfined concrete springs, steel springs) and shear spring will be considered to account for the deformations and the rigid body elements will describe the displacements of the columns and frame when it is subjected to monotonic loading. In this research, single columns will be analyzed first before proceeding into analyzing frame. The experimental results provided by PEER Column Database will be used for the validation of columns. The results using RBS-DEM shows reasonable results for the columns since it closely enveloped the force-displacement curve of the experiment and can be consider as a good validation. For the validation of frame, the work of Yunfei, et a1. (1986) will be used wherein a 3-storey 2-bays frame was analyzed. The monotonic curve of pushover analysis for the tested frame also enveloped the hysteretic curve of the experimental result and can be consider as a reasonable result. The two validations showed a good result since the monotonic curve obtain from pushover analysis closely bounded the hysteretic loops of the experimental results or at least it envelopes the hysteretic curves. Since the results for the two validations were reasonable, it can be concluded that the RBS-DEM is accurate to determine the behavior of reinforced concrete structures.